Inside Cover: Positional Enrichment by Proton Analysis (PEPA): A One‐Dimensional 1H‐NMR Approach for 13C Stable Isotope Tracer Studies in Metabolomics (Angew. Chem. Int. Ed. 13/2017). Issue 13 (2nd March 2017) - Vinaixa, Maria; Rodríguez, Miguel A.; Aivio, Suvi; Capellades, Jordi; Gómez, Josep; Canyellas, Nicolau; Stracker, Travis H.; Yanes, Oscar
Abstract : Elucidating the flow of chemical moieties through the complex set of metabolic reactions in the cell is essential for understanding the regulation of cell metabolism in health and disease. In their Communication on page 3531 ff., M. Vinaixa, O. Yanes et al. report a novel technique for extending high‐throughput 1 H‐1D‐NMR metabolic profiling to stable isotope tracing. This approach expands the range of isotopically enriched metabolites detected in cellular extracts beyond 13 C‐NMR and 2D‐NMR experiments, thus accelerating the implementation of NMR spectroscopy in cell metabolism studies.